Gaining insight into the photophysical properties of a coumarin STP ester with potential for bioconjugation. - González-Pérez, Marina (2019)
The photophysical properties of coumarin 392 4-sulfotetrafluorophenyl ester, C392STP (sodium (E/Z)-4-(4-(2-(6,7-dimethoxycoumarin-3-yl)vinyl)-benzoyl)-2,3,5,6-tetrafluoro-benzenesulfonate) an amine reactive coumarine with potential for bioconjungation, have been studied in different solvents. Strong red shifts (31 to 56 nm on going from dioxane to DMSO and PBS, respectively) were observed in the emission spectra by increasing the solvent polarity while the absorption spectra remain slightly changed. It was found that in addition to non specific solute-solvent interactions, in protic solvents specific interactions such as hydrogen-bonding occur. The photophysical behaviour of coumarin also pointed out to an increase of the polarity of the molecule upon excitation. The molar absorption coefficient, ε385 = 1.03 ˑ 104 M-1cm-1 and brigtness, ε x Φ = 1.18 ˑ 103 M-1cm-1, of the coumarin ester were found to be moderate in PBS even if the fluorescence quantum yield (Φ = 0.115) was found to be relatively low. The large stokes shifts (Δλ = λem-λ abs were found to increase from 74 nm in dioxane to 136 nm in PBS), the photostability and pH insensitivity are characteristics that turn C392STP, into a promising fluorescent dye with potential applications in different fields.